Design and implement a PID temperature controller system for the Air Flow Temperature Control System unit using the Matlab RTW (Real-Time Workshop) tool (MASKAY, 2012)
This project "DESIGN AND IMPLEMENTATION OF A PID TEMPERATURE CONTROLLER SYSTEM FOR THE AIR FLOW TEMPERATURE CONTROL SYSTEM UNIT USING THE MATLAB RTW (REAL TIME WORKSHOP) TOOL," covers the study of the RTW tool where the architecture was analyzed, the algorithm, the process and the stages in the development of a model in real-time through the SIMULINK® system of MATLAB®, in addition, an HMI was made which through .mdl subsystems developed in SIMULINK® allowed the identification of the plant, the experimental PID control and the simulation of the PID control, using for this the Nationals Instruments PCI 6221 data acquisition and generation card, which, after having configured it, allowed the actual plant to be interconnected with the developed HMI subsystems.
Keywords: RTW; real-time; PID; PCI; HMI; Ziegler Nichols